Ambiguous Subjects: The Autobiographical Situation and the Disembodiment of 1968 - Joffroy, Michelle (Confluencia (Greeley, Colo.), 2005)
The unifying force in the novel is Susanas attempt to read and "tell" her self in the context of a complex social reality. [...]the text is dominated by a specific situation that privileges Susana as borh subject and object of the text.13 Critical scrutiny of Pánico o peligros firsr person narrative has resulted in an almost unanimous consensus about the feminist dimension of the novel and its grounding in the feminist practice of autobiographical writing.14 Shifting the theoretical perspective away from a one-to-one correlation between author and text, and toward the fictionalization of the autobiographical act, I argue that it is Susana - and not Maria Luisa Puga - who is engaged in an autobiographical project. Early in the novel Susana refers to the years 1964-65 and imagines tú as a seventeen year-old who was "finishing high school." Ultimately these models reveal the possibilities of more relevant spaces for and ways of reading 68 in a contemporary Mexico. [...]when Lourdes recommends that Susana read the novel One Hundred Years of Solitude - in an unabashed project of "educating" Susana about her political and historical identity - Susan is put off by the novel's density of language, by the basic lack of space for engaging with the text or imagining herself as implicated in it. Unlike [die 1958-9 Railroad workers' strike and die 1965 Doctors' strike] there was no lag time between the initial event and condemnation of civilian participants by press, radio and television." [...]the lag time between the "historical" moment and the "representational" moment - the moment at which some narrative is constructed not only to "report" the event, but to characterize it, impose a meaning, construct its truth - was relatively brief, practically immediate.